Synthesis and Characterization of Silicon Nanoparticles from Coal Fly Ash Using Ultrasonication as a Battery Anode - Robiansyah; Bow, Yohandri; Dewi, Tresna (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Fly ash, a byproduct of coal combustion, is rich in silica, alumina, and other minerals, making it a valuable resource for extracting high-purity silicon. The synthesis of silicon nanoparticles from coal fly ash involves several critical steps, including the extraction of silica (SiO2) via the sol-gel method, reduction of silica to silicon using the metallothermic method, and subsequent ultrasonication to achieve nanoscale particles. Studies have shown that fly ash can contain up to 49.21% silica, which can be further purified to 93.52% via chemical extraction methods such as acid leaching and alkali dissolution. The reduction of silica to silicon is carried out using the metallothermic method, which involves the use of magnesium-reducing agents to convert SiO2 to elemental silicon. This process produces silicon with a purity of about 61.3%, which can be further increased through ultrasonication. Ultrasonication is a technique that uses high-frequency sound waves to break particles into smaller sizes, resulting in more uniform and homogeneous nanoparticles. In this study, ultrasonication for 60 and 120 min reduced the average particle size of silicon from 208.94 nm to 58.87 nm and 20.13 nm, respectively, and increased the silicon content to 74.6% and 72.7%. X-ray diffraction (XRD) and distribution particle analyses confirmed the particle size reduction and homogeneity of silicon nanoparticles, indicating the effectiveness of ultrasonication in producing high-quality silicon nanoparticles. The synthesized silicon nanoparticles have significant potential applications, particularly as anode materials in lithium-ion batteries, due to their increased surface area and improved electrochemical properties. Furthermore, the use of fly ash as a raw material for the synthesis of silicon nanoparticles not only provides a cost-effective and environmentally friendly alternative to traditional silica sources but also helps in reducing the environmental impact of fly ash disposal. The integration of the methods and findings of this study underscores the feasibility and benefits of using coal fly ash for the sustainable production of silicon nanoparticles, which can be utilized in energy storage as anode materials in lithium-ion batteries.